MicroRNA-34c-3p is an early predictive biomarker for doxorubicin-induced glomerular injury progression in male Sprague-Dawley rats. Issue 5 (15th July 2014) - Church, Rachel J.; McDuffie, J. Eric; Sonee, Manisha; Otieno, Monicah; Ma, Jing Ying; Liu, Xuejun; Watkins, Paul B.; Harrill, Alison H.
Graphical Abstract: Abstract: Recently, eight urinary protein biomarkers were qualified for renal toxicity prediction in drug development; however, there are no biomarkers unique to glomerular toxicity. Albuminuria is a hallmark biomarker for primary glomerular injury but lacks specificity. MicroRNA species associated with genes that regulate kidney injury could potentially be used as biomarkers of nephrotoxicity. In this study, microRNA and protein expression changes in urine, blood, and/or kidneys, in addition to histopathology were evaluated in male Sprague-Dawley rats following weekly intravenous injections of doxorubicin (5 mg kg −1 per dose). Following the first administration, urinary miRNA-34c-3p was significantly increased on day 2 and remained elevated on day 7. Urinary osteopontin was significantly increased on day 2 only. Significant urinary albumin was detected on day 7, in the absence of histopathological findings. Following a second doxorubicin administration on day 7, significantly increased urinary kidney injury molecule 1, cystatin C, β2-microglobulin, total protein, and neutrophil gelatinase-associated lipocalin concentrations were detected on day 14. These alterations were concurrent to significant and progressive albuminuria, urinary miR-34c-3p, remarkable microscopic primary glomerular injury and secondary tubular alterations. Urinary miR-34c-3p elevations were predictive of histopathologic injury progression and outperformed the traditional renal biomarkers, serum creatinine and blood urea nitrogen, which did not increase with treatment. MiR-34c-3p was also significantly enriched in damaged glomeruli compared to adjacent nonglomerular tissue. Taken together, miR-34c-3p was identified as a highly sensitive candidate renal safety biomarker with relative specificity, particularly for early prediction of doxorubicin-induced glomerular injury progression in male Sprague-Dawley rats.